Automated Vertical Farming System in Urban Areas: an Urban Farming Solution for Future Food Security - Ningsih, Gumoyo Mumpuni; Rasyid, Harun; Ningsih, Natali; Pujotomo, Darminto; Suseno, Gijanto Purbo (Ridwan Institute, 2025)
Population growth in urban areas has resulted in a decrease in agricultural land and an increase in food dependence from outside the region. This poses a risk to the city's food security. This study aims to analyze the effect of the implementation of automation-based vertical farming systems on improving the food security of urban communities. The research was conducted in a quantitative descriptive manner with a survey approach on 100 respondents of urban farming households in Jakarta. Data were collected through questionnaires and analyzed using simple linear regression to measure the relationship between the use of automation technology (X) and food security levels (Y). The results of the study show that automatic vertical farming systems have a positive and significant influence on household food security, especially in the aspect of food supply availability and sustainability. These findings strengthen the argument that technology-based urban farming is the future solution for big cities in maintaining food security in a sustainable manner. Therefore, the integration of technology in the urban agricultural system needs to be expanded and supported through public policies.